Artificial Intelligence and National Security: Future Warfare Implications for Pakistan - Farid, Armaghan; Sarwar, Ghulam (Annals of Human and Social Sciences, 2024)
This paper is an attempt to analyze the existing capabilities of AI technology within Pakistan’s national security. Artificial Intelligence is the fourth industrial revolution that is offering opportunities from military to economic. The ongoing competition between Russia, China, and the USA is surprisingly attracting the attention of developing states and many view it as it will somehow disrupt the balance of power in international politics. Therefore, this paper is an attempt to understand AI integration in the military as a strategy for national security and its impacts on the balance of power among states. This is a qualitative content analysis research study uses the approach of exploratory research as well as implements the securitization theory and RSCT model in the theoretical framework. This paper identifies that AI use in Arms race and future warfare can effectively ensure national security and bring substantial consequences for military applications transforming the battlefield, altering the nature and character of war.